Adrenergic Myocarditis in Pheochromocytoma - Bonacina Edgardo; Milazzo Angela; Pedrotti Patrizia; Roghi Alberto; Bucciarelli-Ducci Chiara (Journal of Cardiovascular Magnetic Resonance, 2011)
Abstract The clinical presentation of pheochromocytoma is variable and many biochemical and imaging methods have been suggested to improve the diagnostic accuracy of what has been termed "the great masquerader". This case-report is of a middle-aged woman with a non-specific clinical presentation suggesting acute coronary syndrome or subacute myocarditis. Cardiovascular magnetic resonance (CMR) at presentation showed myocardial edema and intramyocardial late gadolinium enhancement (LGE). An adrenal mass was seen, which was confirmed as pheochromocytoma and surgically removed. Our case shows evidence for acute adrenergic myocarditis, with resolution of both the edema and the LGE after surgical excision.